Induction of apoptosis and G2/M cell cycle arrest by Scrophularia striata in a human leukaemia cell line. (29th October 2013) - Azadmehr, A.; Hajiaghaee, R.; Mazandarani, M.
Abstract: Objectives: Scrophularia striata Boiss (Scrophulariaceae) is a plant that grows in northeastern Iran; it has been used traditionally to treat various inflammatory disorders. This study was designed to investigate cytotoxic effects of S. striata extract, on the Jurkat human leukaemia cell line (T‐cell leukaemia). Materials and methods: Phytochemical assay by thin layer chromatography and 2, 2 diphenyl‐1‐picryl‐hydrazyl were used to evaluate main compounds and antioxidant capacity of the plant extract, respectively. Its inhibitory effect on Jurkat cells was evaluated by MTT assay. In addition, cell cycle distribution and apoptotic cell death were evaluated by propidium iodide and annexin V‐FITC/ propidium iodide staining. Results: These showed that the main components present in S. striata extract included flavonoids, phenolic compounds and phenyl propanoids. Treatment with extract was significantly cytotoxic to the tumour cell line. In addition, flow cytometry analysis indicated that S. striata extract induced cell cycle arrest in G2 /M phase and apoptosis of tumour cells. Conclusions: Results of the study indicated that S. striata extract could inhibit leukaemia cell proliferation by inducing G2 /M phase arrest and apoptosis.